Penerapan Metode Think Talk Write (TTW) Dalam Pembelajaran Bahasa Indonesia Pada Materi Menganalisis Unsur Instrinsik Buku Fiksi Terhadap Siswa Kelas VII (Studi Kasus: SMPN 2 Telagasari) - Romlah, Siti; Setiawan, Hendra; Nuraini, Cut (Peneliti.net, 2024)
Indonesian is an important language that is one of the main languages and must be learned from the education level, whether formal or non-formal. One of the efforts to develop Indonesian science is to improve literacy culture through types of stories from Fiction Books. In the learning process, students should be able to master the material and improve their learning activities through understanding the intricate elements in the story in a fiction book. But in fact teaching and learning activities are less effective because teachers provide a lot of theory without a practical process which makes the lack of opportunities for students to put their thoughts into assignments and conduct a discussion between groups, this is also an obstacle to student learning outcomes at SMP Negeri 2 Telagasari, students become unenthusiastic in learning and the absence of motivation makes grades decrease below KKM. Then the TTW method was applied which aimed to support the learning ability of grade VII students of SMP Negeri 2 Telagasari by taking samples of 64 students in class VII B as an experimental class and class VII C as a control class. With the application of the TTW method, the average result (mean) obtained in the control class posttest results of 82.38, while the experimental class posttest was 90.50, then the results of the t-test showed a value of 25.563 with df 62 and a P value of 0.00, so by looking at these results, it can be said that there is a significant difference from the experimental class using the Think Talk Write method and the control class with the Conventional method in the ability of students to write intrinsic elements in fiction books.